Epothilone B Facilitates Peripheral Nerve Regeneration by Promoting Autophagy and Migration in Schwann Cells - Zhou, Jianhua; Li, Shengyou; Gao, Jianbo; Hu, Yawei; Chen, Shaochu; Luo, Xinle; Zhang, Hao; Luo, Zhuojing; Huang, Jinghui (Frontiers in Cellular Neuroscience, 2020)
Seeking for effective drugs which are capable of facilitating axonal regeneration and elongation after peripheral nerve injury has attracted extensive attention. Epothilone B (EpoB) is a FDA-approved antineoplastic agent, which shows capability in inducing α-tubulin polymerization and enhancing microtubule stability. Recently, the neuroprotective effect of EpoB has been increasingly recognized in the central nervous system. However, limited information has been available for the potential therapeutic effect of EpoB on peripheral nerve regeneration. Here, we found that EpoB strikingly improved axonal regeneration and functional recovery in a rat model of sciatic crush injury. In addition, EpoB (1 nM) did not result in significant apoptosis in Schwann cells (SCs), and showed little effect on their viability either. Interestingly, EpoB (1 nM) significantly enhanced migration in SCs, which was inhibited by autophagy inhibitors (3-MA). Since PI3K/Akt signaling has been implicated in regulating autophagy, we further examined the involvement of PI3K/Akt in the process of EpoB-induced SCs migration. It was found that EpoB (1 nM) significantly inhibited phosphorylation of PI3K and Akt in SCs. Further studies showed that both EpoB-enhanced migration and autophagy was increased/inhibited by inhibition/activation of PI3K/Akt signaling with LY294002 or IGF-1. In conclusion, EpoB is capable of promoting axonal regeneration after peripheral nerve injuries by enhancing migration of SCs, which was regulated by PI3K/Akt signaling-mediated autophagy in SCs. Those findings highlight the potential therapeutic value of EpoB in enhancing regeneration and function recovery in the settings of peripheral nerve injuries.